Lifestyle trends and housing typologies in emerging multicultural cities - Salama, Ashraf M.; Wiedmann, Florian; Ibrahim, Hatem G. (Journal of Architecture and Urbanism, 2017)
The introduction of new housing typologies in emerging cities is rooted in dynamics including infrastructural investments, urban growth rates and new development policies. In accommodating new lifestyles, demand-driven patterns by tenants and property owners are the main factors consolidating development trends in future. This paper explores the relationship between new lifestyle patterns and housing typologies in emerging cities. Within the context of Gulf cities, namely Dubai, Abu Dhabi, Doha and Manama, this paper investigates demographic structures and housing trends where a rapid phase of urban growth has transformed local urbanism. Current social structures were analysed by following a new ‘lifestyle framework’ resulting in the characterization of four main lifestyle trends. This is coupled with the assessment of 240 cases of new residences from the Gulf cities under study. The juxtaposition of both studies offers an outlook relevant to the importance of a transition from supply-driven to demand-driven housing dynamics to accommodate emerging multicultural societies. The paper thus contributes to a better understanding and identification of the social groups that are currently lacking suitable housing.